Recent Advances in the Treatment of Breast Cancer - Tong, Christy W. S.; Wu, Mingxia; Cho, William C. S.; To, Kenneth K. W. (Frontiers in Oncology, 2018)
Breast cancer (BC) is the most common malignancy in women. It is classified into a few major molecular subtypes according to hormone and growth factor receptor expression. Over the past few years, substantial advances have been made in the discovery of new drugs for treating BC. Improved understanding of the biologic heterogeneity of BC has allowed the development of more effective and individualized approach to treatment. In this review, we provide an update about the current treatment strategy and discuss the various emerging novel therapies for the major molecular subtypes of BC. A brief account of the clinical development of inhibitors of poly(adenosine diphosphate-ribose) polymerase, cyclin-dependent kinases 4 and 6, PI3K/Akt/mTOR pathway, histone deacetylation, multi-targeting tyrosine kinases and immune checkpoints for personalized treatment of BC is included. However, no targeted drug has been approved for the most aggressive subtype – triple negative BC (TNBC). Thus, we discuss the heterogeneity of TNBC and how molecular subtyping of TNBC may help drug discovery for this deadly disease. The emergence of drug resistance also poses threat to the successful development of targeted therapy in various molecular subtypes of BC. New clinical trials should incorporate advanced methods to identify changes induced by drug treatment, which may be associated with the upregulation of compensatory signaling pathways in drug resistant cancer cells.